2021
DOI: 10.1111/bju.15413
|View full text |Cite
|
Sign up to set email alerts
|

Time interval from transurethral resection of bladder tumour to bacille Calmette–Guérin induction does not impact therapeutic response

Abstract: To investigate bacille Calmette-Gu erin (BCG) tolerability and response with respect to the timing of BCG administration after transurethral resection of bladder tumour (TURBT) in patients with non-muscle-invasive bladder cancer (NMIBC). Patients and MethodsA review of patients with NMIBC at our institution managed with at least 'adequate BCG' (defined by the United States Food and Drug Administration as at least five of six induction instillations, with two additional instillations comprising either maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A European group found that initiation of BCG within 6 weeks of TURBT was associated with a lower rate of cancer recurrence than when BCG treatment was initiated at a later time point [105,106]. Conversely, in an American study of 518 patients time to initiation of BCG after TURBT was not significantly associated with therapeutic response [107].…”
Section: Progression-free Survivalmentioning
confidence: 99%
“…A European group found that initiation of BCG within 6 weeks of TURBT was associated with a lower rate of cancer recurrence than when BCG treatment was initiated at a later time point [105,106]. Conversely, in an American study of 518 patients time to initiation of BCG after TURBT was not significantly associated with therapeutic response [107].…”
Section: Progression-free Survivalmentioning
confidence: 99%
“…In a recent study (Can Urol Assoc J, 2021, 15(8):230–239), 6 , 16 researchers collected the interval times of 518 patients, with a median time of 26 days (6–188 days). The patients were divided into 4 groups by quartile, and the results of survival analyses demonstrated that the differences in prognosis were statistically insignificant between these 4 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further clinical trials using 20 or 40 mg MMC with a larger study population are necessary to determine the clinical usefulness of intravesical MMC + Ara‐C therapy in patients with NMIBC. In the present study, treatment strategies with intravesical therapy are discussed, especially in patients with intermediate‐risk NMIBC [ 26 , 27 ]. We believe that our present results provide important information for discussion on this issue.…”
Section: Discussionmentioning
confidence: 99%